Using factor analysis to identify the factors affecting the causes of delayed pregnancy in Sulaymaniyah Governorate - Azad Abdullah Saeed (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The research aims to study and analyze the influential factors which cause delayed pregnancy them according to their impact on sample containing (80) patients in visited ALI KAMAL hospital in Sulaimanya. The statistical data of the community were collected by the questionnaire and interviews conducted by the doctor in that field. The study population consisted of (400) patients with a physician, 120 patients accepted the form and 80 (completed) (40) non-integrated ,selected by simple randomized eye method, The research has come to a result that the patients has period of time to tried , The sacs in the womb, smoking at close place, worry’s patients, age, Monthly cycle for women factors have the greater impact in increasing causing for disease , while the other factors comes in later rank , finally some recommendation have been presented due to it , like visiting patients to Doctors Specialist .